True and Apparent Scaling: The Proximity of the Markov- Switching Multifractal Model to Long-Range Dependence - Ruipeng Liu; Tiziana Di Matteo; Thomas Lux (Kiel University, Department of Economics, 2007)
In this paper, we consider daily financial data of a collection of different stock market indices, exchange rates, and interest rates, and we analyze their multi-scaling properties by estimating a simple specification of the Markov- switching multifractal model (MSM). In order to see how well the estimated models capture the temporal dependence of the data, we estimate and compare the scaling exponents H(q) (for q = 1; 2) for both empirical data and simulated data of the estimated MSM models. In most cases the multifractal model appears to generate `apparent' long memory in agreement with the empirical scaling laws.
Keywords: 330; Generalized Hurst exponent; Multifractal model; GMM estimation; Scaling